Spread Of Beetles Infecting Pine Trees Planted In The Conditions Of The Khorezm Region - Otayev Odilbek Yuldashevich; Xudayberganov Norbek Atabaevich (Euro Asian Journal Publishing, 2023)
This article describes the distribution of pine bark beetles in the conditions of the Khorezm region and their bioecological features of the form of pine lesion.
Keywords: Beetle; Pine; damage; fog